Working-Through: Reconciliation Efforts of Trauma in Novel A Monster Calls, By Patrick Ness - Arifin, Arifin (Riwayat: Educational Journal of History and Humanities, 2025)
Literary works with psychological themes related to trauma are scattered and are targeting many readers, including one among them teenagers. This research tries to see how traumatic events can occur, what things can be triggers, and how individuals can be freed from trauma through youth literature, namely A Monster Calls. The theory used in this research is the theory from La Capra about Acting-out and Working-through. These two concepts are concepts that are closely related to individuals and collectives who repress trauma or who try to be free from traumatic events that occurred in their past. The results of this study found that there are many aspects that can cause a teenager to experience a traumatic event. In A Monster Calls, aspects that can be the cause of an individual experiencing trauma namely, the absence of the caregiver, physical abuse, psychological violence, neglect or abandonment, witness of domestic violence, as well as victims of divorce. Meanwhile, the symptoms of trauma that arise are irritability, inability to control emotions, distrust, other blaming, feeling isolated, deep guilt and sadness, anxiety and sleep disturbances, as well as nightmares and hallucinations that keep recurring. In dealing with and being free from trauma, individuals need to reconstruct their memories so that they can get a complete picture to be able to accept events that occurred in their past. Reconstructing trauma in A Monster Calls is done through written media, information exchange and the creation of imaginary characters.